In too deep [compact disc, unabridged] - Krentz, Jayne Ann (Krentz, Jayne Ann. Looking glass trilogy, 2010)
Scargill Cove is the perfect place for Fallon Jones, confirmed recluse and investigator of the paranormal. Now someone else has been drawn to the Cove: Isabella Valdez, who is on the run from some very dangerous men. When she starts working as Fallon's assistant, Isabella impresses him by organizing his pathologically chaotic office. But after a routine case unearths an antique clock, Fallon and Isabella are dragged into the secret history of Scargill Cove.